2018
DOI: 10.25011/cim.v41i1.29460
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of fetuin B is associated with osteoporosis: a 4-year prospective study in China

Abstract: Serum fetuin B levels increased with the development of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It is increased in patients with type 2 diabetes and impairs insulin sensitivity in myotubes and hepatocytes ( 76 , 77 ). A 4-year prospective study in China showed serum level of fetuin-B is associated with osteoporosis ( 78 ). Nevertheless, research on the role of fetuin-B in bone metabolism remains limited, both in vivo and in vitro .…”
Section: Hepatokines: From Liver To Bonementioning
confidence: 99%
“…It is increased in patients with type 2 diabetes and impairs insulin sensitivity in myotubes and hepatocytes ( 76 , 77 ). A 4-year prospective study in China showed serum level of fetuin-B is associated with osteoporosis ( 78 ). Nevertheless, research on the role of fetuin-B in bone metabolism remains limited, both in vivo and in vitro .…”
Section: Hepatokines: From Liver To Bonementioning
confidence: 99%